Menelisik Prinsip Beneficial Ownership dalam Kebijakan Pembaruan Hukum Pidana - Subaidah Ratna Juita; Efi Yulistyowati; Supriyadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The principle of beneficial ownership relating to criminal acts committed by corporate administrators is something that is relatively new in Indonesia, so it is interesting to analyze. Analysis regarding this matter cannot be separated from the policy of reforming criminal law with criminal liability for corporations which has been formulated in Law Number 1 of 2023 concerning the Criminal Code and has become a reference and refinement in special criminal law provisions. The focus of this research is related to the development of criminal law policy, especially regarding the principle of beneficial ownership. Beneficiary Ownership is of particular concern because often in law enforcement related to criminal acts committed by corporations, these Beneficial Owners are not touched by the law. The aim of the research carried out by the author is how to identify parties who can be qualified as beneficial owners and what the criminal liability of these beneficial owners is in crimes committed by corporations. This research uses a juridical-normative approach as the main approach. The main object of this research is secondary data which includes primary legal materials and secondary legal materials. Meanwhile, data analysis was carried out using qualitative analysis methods. The results of the discussion of the problems in this research show that there is a close relationship between beneficial owners (Beneficiary Ownership) and corporate legal actions as legal subjects, often beneficial ownership through orders to corporate management to carry out legal actions in their interests. The legal actions carried out by the corporate management reflect the actions of a corporation so that all its implications can make the corporation a legal subject that can be held criminally liable.